A Quantitative Study on the Implementation of the Constructivist Approach and Its Impact on Students' Critical Thinking Skills - Syafrizal Siregar; Irvan Irvan (JMEA : Journal of Mathematics Education and Application, 2025)
Mathematics is often perceived as an abstract and difficult subject by students, especially when learning topics such as Sequences and Series. The constructivist approach is considered effective in helping students build their own understanding through active involvement in the learning process, which in turn enhances their critical thinking skills. This study aims to quantitatively evaluate the impact of implementing a constructivist approach on students’ critical thinking skills in mathematics learning. A pre-experimental one-group pretest-posttest design was used, involving 32 tenth-grade students from the Industrial Computer and Network Engineering (TKJ Industri) program at SMKS Muhammadiyah 9 Medan in the 2024/2025 academic year. Data were collected using critical thinking tests administered before and after the learning intervention. Analysis involved descriptive statistics, normality tests, paired sample t-tests, and N-Gain calculations. Results indicated a significant improvement in students’ critical thinking scores, with the average score increasing from 54.06 to 77.19. The paired sample t-test yielded a significance value of 0.000 (p 0.05), and the N-Gain score was 0.50, indicating a moderate level of effectiveness. These findings suggest that implementing the constructivist approach positively impacts students' critical thinking development.